Effect of Ciprofibrate on Platelet Aggregation and Fibrinolysis in Patients with Hypercholesterolaemia - Simpson, Iain A; Lorimer, A Ross; Walker, Isobel D; Davidson, John F (Thrombosis and Haemostasis, 1985)
The fibrinolytic and platelet effects of Ciprofibrate, a new lipid lowering drug, were studied in 7 patients with hypercholesterolaemia over a 12 week period. A significant reduction in plasma fibrinogen was noted and a lesser increase in fibrinolytic activity. However, no change in platelet aggregation was noted. As expected Ciprofibrate produced a significant hypolipidaemic effect in these patients.We have described effects of Ciprofibrate which may have potential benefits in this high risk patient group.
Keywords: Ciprofibrate; Hypolipidaemic agent; Fibrinolytic activity; Fibrinogen; Hypercholesterolaemia